越南汉语学习者低龄化趋势：成因与现状分析——以胡志明市商业华语培训中心为例 - Dang Thu Lan; Li Qian (Sinolingua: Journal of Chinese Studies, 2024)
In recent years, there has been a noticeable trend of younger learners taking up Chinese globally. Since the Vietnamese Ministry of Education included Chinese as an elective foreign language in primary schools in 2021, the number of primary and secondary school students learning Chinese has significantly increased. To gain a more comprehensive understanding of the current state of Chinese learning in Vietnamese primary and secondary schools, identify potential challenges in the process of younger learners taking up Chinese, and provide valuable data support for the formulation of long-term Chinese education development plans, this study uses the Hoavan SHZ Chinese Training Center as a case study. It explores the enrollment situation and operational status of young learners over the past ten years. Through data analysis and interviews, the study examines changes in the age groups of young learners, the causes of the trend toward younger learners, the prospects for development, and the challenges faced. The results show that the number of young Chinese learners in Vietnam has been steadily increasing, with the age of learners continuously decreasing, including preschool children starting to learn Chinese. National education policies and the deepening of China-Vietnam cooperation are the main driving forces. To respond to this trend and meet the needs of parents and students, this paper advocates cultivating students' interest in learning, improving the quality of teachers, and refining teaching materials and methods.